Mandated or Voluntary Treatment of Men Who Committed Child Sexual Abuse: Is There a Difference? - von Franqué, Fritjof; Briken, Peer (Frontiers in Psychiatry, 2021)
Child sexual abuse is mostly associated with multiple and sometimes severe consequences for people who are affected by it. Therefore, its prevention represents an important objective. One of the strategies used for this purpose is the treatment of people who have sexually abused children, with the assumption that there is often a risk for reoffending. However, there is still very limited knowledge about how men who have not been convicted of child sexual abuse but participate in voluntary treatment (here called non-forensic clients) differ from those who are convicted and undergo mandated treatment (here called forensic clients). This study compared 22 forensic and 22 non-forensic clients regarding pedophilic interests, static and dynamic risk factors, responsivity features, and treatment progress during an individualized treatment based on the principles of risk, need, and responsivity. We found neither differences in the rates in the DSM-5 diagnosis of pedophilic disorder, nor in risk and responsivity associated scores at the beginning of treatment. In both groups, a low to moderate risk for sexual re-offending was estimated. Both groups improved their functioning on dynamic risk and responsivity factors under treatment. Non-forensic clients had a higher amount of responsivity associated resources than forensic clients. The limitations of these results and their implications for further research and prevention approaches are discussed.